The Effectiveness and Cost‐Effectiveness of Spinal Cord Stimulation for Refractory Angina (RASCAL Study): A Pilot Randomized Controlled Trial. Issue 1 (21st September 2015) - Eldabe, Sam; Thomson, Simon; Duarte, Rui; Brookes, Morag; deBelder, Mark; Raphael, Jon; Davies, Ed; Taylor, Rod
Abstract : Background: Patients with "refractory angina" (RA) unsuitable for coronary revascularization experience high levels of hospitalization and poor health‐related quality of life. Randomized trials have shown spinal cord stimulation (SCS) to be a promising treatment for chronic stable angina and RA; however, none has compared SCS with usual care (UC). The aim of this pilot study was to address the key uncertainties of conducting a definitive multicenter trial to assess the clinical and cost‐effectiveness of SCS in RA patients, i.e., recruitment and retention of patients, burden of outcome measures, our ability to standardize UC in a UK NHS setting. Methods: RA patients deemed suitable were randomized in a 1:1 ratio to SCS plus UC (SCS group) or UC alone (UC group). We sought to assess: recruitment, uptake, and retention of patients; feasibility and acceptability of SCS treatment; the feasibility and acceptability of standardizing UC; and the feasibility and acceptability of the proposed trial outcome measures. Patient outcomes were assessed at baseline (prerandomization) and three and six months postrandomization. Results: We failed to meet our planned recruitment target (45 patients) and randomized 29 patients (15 SCS group, 14 UC group) over a 42‐month period across four sites. None of the study participants chose to withdraw following consent and randomization. With exception of two deaths, all completed evaluation at baseline and follow‐up. Although the study was not formally powered to compare outcomes between groups, we saw a trend toward larger improvements in both primary and secondary outcomes in the SCS group. Conclusions: While patient recruitment was found to be challenging, levels of participant retention, outcome completion, and acceptability of SCS therapy were high. A number of lessons are presented in order to take forward a future definitive pragmatic randomized trial.